Expression Dynamics of Innate Immunity in Influenza Virus-Infected Swine - Montoya, María; Foni, Emanuela; Solórzano, Alicia; Razzuoli, Elisabetta; Baratelli, Massimiliano; Bilato, Dania; Córdoba, Lorena; del Burgo, Maria Angeles Martín; Martinez, Jorge; Martinez-Orellana, Pamela; Chiapponi, Chiara; Perlin, David S.; et al. (Frontiers in Veterinary Science, 2017)
The current circulating Swine Influenza Virus (IV) subtypes in Europe (H1N1, H1N2 and H3N2) are associated with clinical outbreaks of disease. However, we showed that pigs could be susceptible to other IV strains that are able to cross the species barrier. In this work, we extended our investigations into whether different IV strains able to cross the species barrier might give rise to different innate immune responses that could be associated with pathological lesions. For this purpose, we used the same samples collected in a previous study of ours, in which healthy pigs had been infected with a H3N2 Swine IV and four different H3N8 IV strains circulating in different animal species. Pigs had been clinically inspected and 4 subjects/group were sacrificed at 3, 6 and 21 days post infection. In the present study, all groups but mock exhibited antibody responses to IV NP protein. Pulmonary lesions and high-titered viral replication were observed in pigs infected with the swine-adapted virus. Interestingly, pigs infected with avian and seal H3N8 strains also showed moderate lesions and viral replication, whereas equine and canine influenza viruses did not cause overt pathological signs, and replication was barely detectable. Swine IV infection induced IFN-alpha and IL-6 responses in bronchoalveolar fluids at day 3 post infection, as opposed to the other non-swine adapted virus strains. However, IFN-alpha responses to the swine-adapted virus were not associated with an increase of the local, constitutive expression of IFN-alpha genes. Remarkably, the Equine strain gave rise to a Serum Amyloid A response in bronchoalveolar fluids despite little if any replication. Each virus strain could be associated with expression of cytokine genes and/or proteins after infection. These responses were observed well beyond the period of virus replication, suggesting a prolonged homeostatic imbalance of the innate immune system.